2016
DOI: 10.1016/j.ijsolstr.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of viscoelastic soft dielectric elastomer generators operating in an electrical circuit

Abstract: A predicting model for soft Dielectric Elastomer Generators (DEGs) must consider a realistic model of the electromechanical behaviour of the elastomer filling, the variable capacitor and of the electrical circuit connecting all elements of the device. In this paper such an objective is achieved by proposing a complete framework for reliable simulations of soft energy harvesters. In particular, a simple electrical circuit is realised by connecting the capacitor, stretched periodically by a source of mechanical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…[ 55 ] The effect of strain‐dependent mechanical dissipations is considered by means of viscoelastic rheological models, based on which the polymeric materials are rendered as linear networks of hyperelastic elements and dissipative elements. [ 56,57 ] 2) Electrically, the DE material is modeled as a linear dielectric, and the electroelastic interaction is rendered in terms of electrostatic stresses on the DE induced by the electric field (namely, Maxwell stress). [ 36 ] Electrical losses due to the electrodes and the DE material resistivity are accounted for by modeling the DEG as a linear circuit combining capacitive and resistive elements.…”
Section: Generalities On Degsmentioning
confidence: 99%
“…[ 55 ] The effect of strain‐dependent mechanical dissipations is considered by means of viscoelastic rheological models, based on which the polymeric materials are rendered as linear networks of hyperelastic elements and dissipative elements. [ 56,57 ] 2) Electrically, the DE material is modeled as a linear dielectric, and the electroelastic interaction is rendered in terms of electrostatic stresses on the DE induced by the electric field (namely, Maxwell stress). [ 36 ] Electrical losses due to the electrodes and the DE material resistivity are accounted for by modeling the DEG as a linear circuit combining capacitive and resistive elements.…”
Section: Generalities On Degsmentioning
confidence: 99%
“…where W must be a convex function with respect to the extended set V. As shown in Remark 1 below, the new extended set of convex restrictions proved to be a sufficient condition for the satisfaction of the ellipticity condition (10). Shortly after the work in [31], Šilhavý [69] proved that multi-variable convexity, or A-polyconvexity, as he denoted it in his work, in conjunction with suitable growth conditions, ensures existence of minimisers in nonlinear electro-magnetoelasticity.…”
Section: Multi-variable Convexitymentioning
confidence: 91%
“…Dielectric elastomers (DEs) are recognised as one of the most popular Electronic EAPs [43,55,57] due to their outstanding actuation capabilities (i.e., light weight, fast response time, flexibility, low stiffness properties), which makes them ideal for their use as soft robots [3,4,10,13,14,41,46,51,62] or flexible energy generators [42,48]. However, an extremely large electric field is generally required in order to access the large actuation regime in DEs, an aspect that very often places them on the risk of electromechanical instabilities or even electrical breakdown [5].…”
Section: Introductionmentioning
confidence: 99%
“…A model combining in parallel Maxwell and Kelvin-Voight elements has also been suggested [62]. Models based on the generalised Maxwell model, also known as Maxwell-Wiechert model, have also been proposed and implemented [56,63,64]. An extensive review of viscoelastic models can be found in [65].…”
Section: Modellingmentioning
confidence: 99%